A statistical approach to evaluate the chemistry and quality of groundwater in Jamankira area, Sambalpur district, Orissa, India - Jena, J. K.; Verma, P. K.; Sahoo, H. K. (Journal of Nepal Geological Society, 2007)
The groundwater quality in the Jamankira area of Sambalpur district was evaluated to determine its hydrogeochemical variability. A total of thirty groundwater samples were analysed for their major chemical constituents. The quality of groundwater was estimated on the basis of total dissolved solids, sodium adsorption ratio, sodium percentage, residual sodium carbonate, and Piper’s trilinear diagram. Cluster analysis was used in the study as a qualitative means for differentiating the groundwater into distinctive types. The cluster analysis shows: 1) Ca-HCO3-SO4-Mg bearing calcium-rich water and 2) Na - K-Cl bearing sodium-rich water in the study area.